Conductive slurry, gas diffusion layer and preparation method thereof, and hydrogen fuel cell
By using polydopamine as a pore-forming agent in the gas diffusion layer of the hydrogen fuel cell to generate a microporous layer, the problem of fast decomposition of gas diffusion layer materials in the prior art is solved, and higher conductivity and durability are achieved, and the overall performance of the hydrogen fuel cell is improved.
Patent Information
- Application Number
- CN202410858062.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The gas diffusion layer materials in existing hydrogen fuel cells decompose fast at high temperatures, resulting in coating collapse, uneven pore size and poor chemical stability, affecting battery performance and durability.
Polydopamine is used as the pore-forming agent to generate a microporous layer in the conductive paste through in-situ polymerization, controlling the porosity and pore size of the microporous layer, and improving the uniformity and conductivity of the gas diffusion layer.
The surface flatness, conductivity and durability of the gas diffusion layer are significantly improved, and the electrochemical performance and long life of hydrogen fuel cells are improved.
Smart Images

Figure CN118825314B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of hydrogen fuel cells, and specifically relates to a conductive slurry, a method for preparing the conductive slurry, a gas diffusion layer, a method for preparing the gas diffusion layer, and a hydrogen fuel cell. Background Art
[0002] A hydrogen fuel cell is a device that generates electricity by reacting hydrogen and oxygen. Unlike traditional fossil energy sources, the electricity generated by hydrogen fuel cells does not produce harmful gas emissions. It is an environmentally friendly and efficient energy conversion technology. It also has significant advantages such as simple and compact structure, low noise, high reliability, modularization, and rapid response to load changes. It is known as one of the main energy sources of the 21st century and is the fourth generation of power generation after thermal power, hydropower, and nuclear power. At present, hydrogen fuel cells have been widely used in transportation, electricity and energy storage, aerospace navigation, military defense, mobile communications and other fields. It occupies an important position in the transformation of the global energy structure and is one of the important paths for countries to achieve energy security strategies and low-carbon goals. Therefore, researchers have invested a lot of energy in the development of efficient hydrogen fuel cells to meet the future application of systems such as transportation, stationary power generation, and portable power supplies. Compared with lithium batteries, hydrogen fuel cells are more able to meet the needs of long-range, high-temperature, and high-cold working conditions.
[0003] With the continuous construction of hydrogen refueling stations, the improvement of the hydrogen fuel cell industry and the reduction of hydrogen fuel cell system costs, the scale of my country's hydrogen fuel cell market will continue to grow.
[0004] Hydrogen fuel cells currently mainly include alkaline hydrogen fuel cells (AFC), proton exchange membrane hydrogen fuel cells (PEMFC), phosphate hydrogen fuel cells (PAFC), molten carbonate hydrogen fuel cells (MCFC), and solid oxide hydrogen fuel cells (SOFC). Among them, proton exchange membrane hydrogen fuel cells (PEMFC) have attracted much attention in recent years due to their low operating temperature (about 80°C), high power density, fast startup and fast response to load changes. It is also the most widely used type of hydrogen fuel cell.
[0005] The core of proton exchange membrane hydrogen fuel cells is the membrane electrode, which is the core field of multiple material transmission and electrochemical reactions and is figuratively called the "heart" of the fuel cell. However, although the leading companies of my country's major membrane electrode suppliers have achieved independent preparation of membrane electrodes, the core materials are mainly imported, especially the gas diffusion layer, which is the core raw material of hydrogen fuel cells with the lowest localization rate.
[0006] According to the calculation of the U.S. Department of Energy (DOE), in the case of large-scale production (500,000 units / year), the membrane electrode accounts for about 60% of the cost of the fuel cell stack, while the cost of the stack accounts for more than 60% of the fuel cell system, and the fuel cell system accounts for more than 60% of the purchase cost of the hydrogen vehicle. In other words, reducing the cost of the membrane electrode is the core of reducing the cost of the stack and fuel cell system, and reducing the cost of the membrane electrode depends on the localization of core materials. Therefore, more and more domestic enterprises and research institutes have begun to invest a lot of R&D power to overcome their technical barriers to accelerate the localization of core raw materials. The membrane electrode is mainly composed of three parts: catalyst, proton exchange membrane, and gas diffusion layer. Under the corresponding temperature and pressure, hot pressing becomes a three-in-one component, which undertakes all the electrochemical reactions of the fuel cell, as well as the conduction of electrons, protons, gases and water, and determines the performance, life and cost of the stack. High-performance, low-cost, and long-life membrane electrodes are of great significance to accelerate the commercialization of hydrogen fuel cells.
[0007] The fuel gas hydrogen passes through the anode gas diffusion layer to the catalyst layer, and an electrode reaction occurs under the action of the catalyst. The generated electrons flow through the external circuit through the conduction of the catalyst layer to the cathode, and the hydrogen ions reach the cathode under the action of the proton exchange membrane. After passing through the cathode gas diffusion layer, oxygen reacts with hydrogen ions and electrons under the action of the catalyst to generate water. The generated water must be discharged in time to avoid the phenomenon of "flooding the electrode". It can be seen that the gas diffusion layer in the electrode not only plays a role in supporting the catalyst layer and stabilizing the electrode structure, but also has multiple functions of providing gas channels, electron channels and drainage channels for electrode reactions. Therefore, as one of the important components of membrane electrode, the gas diffusion layer (GDL) must meet the following requirements to obtain long-lasting excellent battery performance: 1. Uniform porous structure with good air permeability; 2. Low resistivity and strong electron conductivity; 3. Tight structure and flat surface to reduce contact resistance and improve conductivity; 4. Certain mechanical strength, appropriate rigidity and flexibility, which is conducive to the production of electrodes and provides stability of electrode structure under long-term operation conditions; 5. Appropriate hydrophilic / hydrophobic balance and pore structure to prevent excessive water from blocking the pores and causing a decrease in gas permeability (i.e. "flooding" phenomenon); 6. Chemical stability and thermal stability. The gas diffusion layer substrate materials mainly include carbon fiber paper, carbon fiber woven cloth, carbon fiber non-woven materials, etc., because they have excellent electrical conductivity, thermal conductivity, chemical and thermal stability. However, the large pore structure of the substrate cannot achieve uniform gas transmission and effectively maintain gas-liquid equilibrium, and the poor surface flatness leads to insufficient contact with the catalyst layer, high contact resistance, and defects that easily puncture the proton exchange membrane. Therefore, a conductive microporous layer (MPL) needs to be coated on the carbon fiber, and the design and control of its pore structure plays a crucial role in the comprehensive performance of the gas diffusion layer.
[0008] Table 1: Thermal decomposition rate of various inorganic salts (80℃ / 30 minutes)
[0009] name Initial weight / g Weight after pyrolysis / g Thermal decomposition rate% Ammonium bicarbonate 0.1035 0.0091 91.2% Ammonium carbonate 0.1241 0.0064 94.8% Ammonium acetate 0.0982 0.0000 100.0%
[0010] A Chinese invention patent application with publication number CN102024961A and titled "A gas diffusion layer for a proton exchange membrane fuel cell and its preparation method" discloses a method for preparing a gas diffusion layer for a proton membrane fuel cell, by adding a certain proportion of pore-forming agents, such as ammonium carbonate, ammonium bicarbonate, and ammonium oxalate, to the coating slurry, and then sintering at 340°C after coating to decompose the pore-forming agents to obtain a microporous coating. However, as shown in Table 1, most of these inorganic salts have a low decomposition temperature and a fast decomposition rate, and may have begun to decompose before the coating is completely dry, which can easily cause the coating to collapse and affect the pore structure. At the same time, a large number of bubbles are generated when the inorganic salts decompose, causing cracks on the coating surface, too large pore sizes, and uneven distribution, which seriously affects the electrochemical performance and durability of the battery. Summary of the invention
[0011] The purpose of this application is to provide a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell and a preparation method thereof to overcome the defects of the prior art. By using polydopamine as a pore-forming agent, the surface of the prepared gas diffusion layer is uniform and flat, and has excellent conductivity and durability. The gas diffusion layer described herein is more excellent in water management, has better battery performance, and has a higher current under the same loading voltage.
[0012] In order to solve the above technical problems, this application provides the following technical solutions.
[0013] In a first aspect, the present application provides a conductive paste, wherein the raw material components of the conductive paste include: carbon powder, a first hydrophobic agent, a carbon black dispersant, a pore-forming agent, and a solvent;
[0014] The pore-forming agent is polydopamine generated by in-situ polymerization of dopamine hydrochloride in a weakly alkaline solution environment.
[0015] In one embodiment of the first aspect, the carbon powder accounts for 30 to 70% by weight of the solid content of the total weight of the conductive paste, preferably 40 to 60%;
[0016] The first hydrophobic agent accounts for 10 to 50% by weight of the solid content of the total weight of the conductive paste, preferably 20 to 40%;
[0017] The carbon black dispersant accounts for 30-70% of the total weight of the carbon powder, preferably 40-60%;
[0018] The pore-forming agent accounts for 10-50% of the total weight of the carbon powder, preferably 25-35%.
[0019] In one embodiment of the first aspect, the carbon powder is selected from one or a mixture of hydrophobically modified carbon black, acetylene black, conductive carbon black XC72, pearl black and Ketjen black.
[0020] In one embodiment of the first aspect, the first hydrophobic agent is PTFE emulsion.
[0021] In one embodiment of the first aspect, the carbon black dispersant is one or more of TEGO 760w, TEGO 755w, Solsperse W210, and Solsperse W205.
[0022] In one embodiment of the first aspect, the solvent is water and one or more selected from the following: ethanol, ethylene glycol, isopropanol and n-propanol.
[0023] In a second aspect, the present application provides a method for preparing the conductive paste as described in the first aspect, characterized in that the method comprises the following steps:
[0024] S10: mixing carbon powder, a first hydrophobic agent, a carbon black dispersant and a solvent to obtain a first mixed solution, and adjusting the pH of the first mixed solution to 7.5 to 10, preferably to 7.5 to 8.5;
[0025] S20: mixing dopamine hydrochloride and the first mixed solution under stirring, and terminating the reaction when the polydopamine reaches a target polymerization degree to obtain the conductive paste.
[0026] In a third aspect, the present application provides a gas diffusion layer, the gas diffusion layer comprising:
[0027] substrate layer;
[0028] and, a microporous layer disposed on the substrate layer;
[0029] The substrate layer comprises a second hydrophobic agent sintered at 340-400° C., the second hydrophobic agent completely penetrates into the interior of the substrate layer, and the upper surface and the lower surface of the substrate layer do not comprise a thin film layer having a certain thickness formed by the second hydrophobic agent;
[0030] Wherein, the microporous layer is made of the conductive paste as described in the first aspect.
[0031] In one embodiment of the third aspect, the microporous layer includes at least a first microporous layer and a second microporous layer, the first microporous layer is closer to the substrate layer than the second microporous layer, and the porosity and pore size of the micropores of the microporous layer gradually decrease along the direction from the first microporous layer to the second microporous layer.
[0032] In one embodiment of the third aspect, the substrate layer includes one or more of the following: carbon fiber paper, carbon fiber non-woven fabric, and carbon fiber braid.
[0033] In one embodiment of the third aspect, when the microporous layer is a single-layer microporous layer, its thickness is 10 to 100 μm, preferably 20 to 80 μm, and more preferably 30 to 70 μm; when the microporous layer is two or more microporous layers, its total thickness is 10 to 100 μm, preferably 20 to 80 μm, and more preferably 30 to 70 μm.
[0034] In a fourth aspect, the present application provides a method for preparing a gas diffusion layer as described in the third aspect, the preparation method comprising the following steps:
[0035] S1, coating the hydrophobic pretreatment layer slurry onto the substrate layer, drying and high-temperature sintering;
[0036] S2, coating the first microporous layer slurry on the sample obtained in step S1, and drying;
[0037] S3, if there are two microporous layers, apply the second microporous layer slurry to the sample obtained in step S2 and dry it;
[0038] S4: Similarly, if there are multiple microporous layers, repeat steps S2 and S3;
[0039] S5. After all coating and drying steps are completed, the coating is placed in a high-temperature oven or muffle furnace for high-temperature sintering.
[0040] In one embodiment of the fourth aspect, the drying is performed at 80-120°C for 5-20 minutes; the high-temperature sintering temperature is 340-400°C, and the sintering time is 10-60 minutes, preferably the high-temperature sintering temperature is 370-380°C, and the sintering time is 30-40 minutes.
[0041] In one embodiment of the fourth aspect, in step S1, the coating is spray coating and dip coating, and in S2 to S4, the coating is screen printing, gravure coating, slit coating, spray coating or blade coating.
[0042] In a fifth aspect, the present application provides a hydrogen fuel cell comprising the gas diffusion layer as described in the third aspect.
[0043] Compared with the prior art, the positive effect of the present invention is that the present invention relates to a gas diffusion layer for a hydrogen fuel cell, which comprises a substrate layer and a microporous layer in sequence, wherein the microporous layer can be a single-layer structure, or a two-layer or multi-layer gradient structure with a gradually decreasing porosity from bottom to top. The slurry used in the preparation process of the microporous layer of the gas diffusion layer described in the technical solution of the present invention adopts in-situ polymerized dopamine as a pore-forming agent, and the porosity and pore size of each microporous layer are controlled by the dopamine addition ratio and the polymerization reaction conditions. The preparation method of the present invention can significantly improve the uniformity, surface smoothness, conductivity and durability of the gas diffusion layer material, and at the same time, the performance of the fuel cell prepared with the gas diffusion layer is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic diagram showing a gas diffusion layer according to one embodiment of the present application.
[0045] Figure 2 A schematic diagram showing a gas diffusion layer according to another embodiment of the present application.
[0046] Figure 3 This is a microscope photograph showing the surface of the substrate layer according to one embodiment of the present application at 100 times magnification.
[0047] Figure 4 A microscopic photograph showing the surface of the gas diffusion layer according to Example 1 when magnified 100 times is shown.
[0048] Figure 5 A microscope photograph showing the surface of a commercial gas diffusion layer at 100 times magnification is shown.
[0049] Figure 6 A scanning electron microscope (SEM) photograph showing the surface of the gas diffusion layer according to Example 1.
[0050] Figure 7 A pore size distribution graph of the gas diffusion layer according to Example 1 is shown.
[0051] Figure 8 The single cell polarization curves using the gas diffusion layers of Examples 1 to 4 and Comparative Examples 1 to 2 are shown.
[0052] Explanation of reference numerals: 1, substrate layer; 2, microporous layer; 201, first microporous layer; 202, second microporous layer. DETAILED DESCRIPTION
[0053] Unless otherwise indicated, implied from the context, or customary in the prior art, all parts and percentages in this application are based on weight, and the test and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application or publication referred to in this application are fully incorporated herein by reference, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, product and processing designs, polymers, comonomers, initiators or catalysts disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.
[0054] Numerical ranges in this application are approximate values, so unless otherwise specified, they may include numerical values outside the range. Numerical ranges include all numerical values from the lower limit to the upper limit increased by 1 unit, provided that there is an interval of at least 2 units between any lower value and any higher value. For example, if the recorded component, physical or other properties (such as molecular weight, melt index, etc.) are 100 to 1000, it means that all single values are clearly listed, such as 100, 101, 102, etc., and all sub-ranges, such as 100 to 166, 155 to 170, 198 to 200, etc. For a range containing a numerical value less than 1 or containing a fraction greater than 1 (such as 1.1, 1.5, etc.), 1 unit is appropriately regarded as 0.0001, 0.001, 0.01 or 0.1. For a range containing a single digit less than 10 (such as 1 to 5), 1 unit is usually regarded as 0.1. These are only specific examples of what is intended to be expressed, and all possible combinations of values between the lowest and highest values listed are considered to be clearly recorded in this application. It should also be noted that the terms "first", "second", etc. in this article do not limit the order of precedence, but are only used to distinguish substances with different structures.
[0055] When used with respect to chemical compounds, unless expressly specified otherwise, the singular includes all isomeric forms and vice versa (e.g., "hexane" includes all isomers of hexane, individually or collectively). In addition, nouns using "a," "an," or "the" also include their plural forms unless expressly specified otherwise.
[0056] The terms "comprising", "including", "having" and their derivatives do not exclude the presence of any other components, steps or processes, and are irrelevant to whether these other components, steps or processes are disclosed in this application. To eliminate any doubt, unless explicitly stated, all compositions using the terms "comprising", "including", or "having" in this application may include any additional additives, adjuvants or compounds. On the contrary, except for those necessary for operating performance, the term "essentially consisting of..." excludes any other components, steps or processes from the scope of any description of the term below. The term "consisting of..." does not include any components, steps or processes that are not specifically described or listed. Unless explicitly stated, the term "or" refers to the listed individual members or any combination thereof.
[0057] In a specific embodiment, Figure 1-3 As shown, the present invention relates to a gas diffusion layer for a hydrogen fuel cell. The gas diffusion layer may sequentially include a substrate layer 1 and a microporous layer 2 arranged on the substrate layer.
[0058] In a specific embodiment, the substrate layer 1 includes a second hydrophobic agent sintered at 340-400° C., the second hydrophobic agent completely penetrates into the interior of the substrate layer, and the upper surface and the lower surface of the substrate layer 1 do not include a film layer with a certain thickness formed by the second hydrophobic agent. Figure 3 , which shows a microscope photograph of the surface of the substrate layer according to one embodiment of the present application when it is magnified 100 times. Figure 3 It can be seen that the second hydrophobic agent does not form a dense film layer on the upper surface of the substrate layer 1. In fact, because the amount of the second hydrophobic agent is small, even if the second hydrophobic material penetrates into the interior of the substrate layer 1, it only adheres to the fiber surface without forming a dense film layer. As an embodiment, the substrate is carbon fiber paper, carbon fiber nonwoven fabric, and carbon fiber braid. The substrate preferably uses carbon fiber paper (referred to as carbon paper) and carbon fiber nonwoven fabric (referred to as carbon cloth).
[0059] As an embodiment, the substrate hydrophobic pretreatment layer is a substrate layer pretreated with a hydrophobic agent to obtain a hydrophobic effect. The hydrophobic agent can be a mixture of one or more of PTFE emulsion, tetrafluoroethylene and hexafluoropropylene copolymer emulsion, polyvinylidene fluoride emulsion, and polytrifluorochloroethylene suspension. The hydrophobic agent preferably uses PTFE emulsion. In some embodiments, the substrate layer is pretreated with a PTFE hydrophobic agent; the mass percentage of PTFE in the substrate layer is 5 to 30%. Specifically, the substrate layer uses porous carbon paper or carbon cloth, which is pretreated with a PTFE hydrophobic agent and sintered at high temperature. After sintering, the mass percentage of PTFE in the substrate is 5 to 30%, and the preferred mass percentage is 10 to 20%. The high-temperature sintering temperature is 340 to 400°C, and the sintering time is 10 to 60 minutes. Preferably, the high-temperature sintering temperature is 370 to 380°C, and the sintering time is 30 to 40 minutes.
[0060] As an implementation scheme, the substrate pretreatment layer needs to completely penetrate into the interior of the substrate layer, and be wrapped around the surface of the carbon fiber filaments after high-temperature sintering. A film layer of a certain thickness cannot be formed on the outer side of the substrate, otherwise the porosity of the substrate layer will be reduced, thereby affecting the air and water permeability.
[0061] exist Figure 1 In the embodiment shown, the microporous layer 2 is a single-layer structure. Figure 2 In the embodiment shown, the microporous layer is a two-layer structure, that is, the microporous layer includes a first microporous layer 201 and a second microporous layer 202, and the first microporous layer 201 is closer to the substrate layer 1 than the second microporous layer 202. In this case, the porosity and pore size of the microporous layer gradually decrease from bottom to top. In other words, the porosity and pore size of the first microporous layer 201 are greater than the porosity and pore size of the second microporous layer 202. Similarly, the microporous layer may also include a third microporous layer (not shown in the figure) disposed above the second microporous layer 202.
[0062] As an embodiment, the microporous layer is a coating coated with one, two or more layers of microporous layer slurry. The microporous layer slurry components include: carbon powder, hydrophobic agent, carbon black dispersant, pore former, solvent. The pore former is polydopamine generated by in-situ polymerization of dopamine hydrochloride added to the microporous layer slurry in a weakly alkaline solution environment and room temperature. The prepared microporous layer slurry is coated on the upper surface of the substrate layer pretreated with a hydrophobic agent, dried at 80 to 120°C for 5 to 20 minutes and sintered at 340 to 400°C for 10 to 60 minutes. The amount of dopamine hydrochloride added to the microporous layer slurry is 10 to 50% of the mass percentage of the carbon powder, and the porosity and pore size of the microporous layer can be adjusted by the dopamine addition ratio and its polymerization reaction time. If the microporous layer has a two-layer or multi-layer gradient pore size structure, the closer the microporous layer is to the substrate side, the higher the porosity and the larger the pore size, the higher the proportion of dopamine hydrochloride added in the slurry and the longer the polymerization reaction time; conversely, the microporous layer close to the air side (the contact surface with the catalyst layer in the membrane electrode) has the lowest porosity and the smallest pore size, the lower the proportion of dopamine hydrochloride added in the slurry and the shorter the polymerization reaction time.
[0063] As an embodiment, the microporous layer is located on any side of the substrate after hydrophobic treatment. If it is a single-layer microporous layer, its thickness is 10 to 100 μm, preferably 20 to 80 μm, and more preferably 30 to 70 μm; if it is a two-layer or multi-layer microporous layer, its total thickness is 10 to 100 μm, preferably 20 to 80 μm, and more preferably 30 to 70 μm.
[0064] As an embodiment, the pore layer slurry components include: carbon powder, hydrophobic agent, carbon black dispersant, pore former, and solvent.
[0065] The carbon powder can be selected from one or a mixture of hydrophobically modified carbon black, acetylene black, conductive carbon black XC72, pearl black and Ketjen black.
[0066] As an embodiment, the hydrophobic agent is PTFE emulsion. The mass percentage of PTFE (solid component in the emulsion) in the substrate hydrophobic pretreatment layer slurry to the solid component of the total weight of the conductive slurry is 10-50%, preferably 20-40%.
[0067] As an embodiment, the carbon black dispersant is one or more of TEGO 760w, TEGO 755w, Solsperse W210, and Solsperse W205.
[0068] As an embodiment, the pore-forming agent is polydopamine. Specifically, the pre-configured microporous layer slurry (carbon powder, hydrophobic agent, carbon black dispersant and solvent mixture) is adjusted to weak alkalinity, and the pH value of the solution ranges from 7.5 to 10, preferably from 7.5 to 8.5; then dopamine hydrochloride is added in a certain proportion, and mechanical stirring is carried out at room temperature for 12 to 72 hours. When exposed to oxygen in the air under weak alkaline conditions, dopamine uses its large number of amino and hydroxyl hydrogen bonds to adsorb to the surface of the carbon powder particles and undergoes in-situ self-assembly polymerization to form polydopamine-carbon powder composite particles. In order to prevent the uncontrolled growth of the composite particles, when the polydopamine reaches the target degree of polymerization, a dilute acid solution is added to terminate the reaction. The prepared microporous layer slurry is coated, dried and sintered at high temperature, and the polydopamine is decomposed at high temperature to form a uniform and dense microporous structure on the surface of the substrate. Since the polymerization reaction of dopamine in a weakly alkaline solution is relatively slow, the particle size of the polydopamine-carbon powder composite particles is easy to control, thereby achieving fine regulation of the pore structure of the microporous layer. The higher the addition ratio of dopamine hydrochloride in the microporous layer slurry, the higher the porosity of the microporous layer; the longer the stirring reaction time of the microporous layer slurry, the larger the polydopamine particle size, and thus the larger the pore size of the microporous layer. Therefore, the pore structure of the microporous layer can be finely controlled and optimized by the addition ratio of dopamine hydrochloride and the polymerization reaction time, and a gradient pore structure can be formed by applying different microporous layer slurries multiple times.
[0069] In addition to the pore-forming effect, polydopamine has the following characteristics: (1) Dopamine is an important component of mussel adhesive protein and belongs to the amine compound. It has very strong adhesion to the surface of materials. The reason for this characteristic is mainly because the amino functional group and catechol in the dopamine molecule can form covalent-non-covalent interactions on the surface of the material under certain conditions, thereby allowing the dopamine molecule to adhere tightly to the surface of the material. In an oxidizing environment, dopamine will spontaneously polymerize in an aqueous solution, in which the catechol functional group is oxidized to quinone, and finally a polydopamine coating will be formed on the surface of the material. In the microporous layer of the gas diffusion layer, PTFE acts as both a hydrophobic agent and a binder, but its surface energy is very low, and it is difficult to form a good bonding force with the surface of carbon powder and carbon fiber. However, the working conditions of fuel cells are very harsh (high temperature, high humidity, acidity, electrochemical corrosion), which makes PTFE easily fall off from the surface of carbon powder and carbon fiber, thereby reducing the hydrophobicity of the gas diffusion layer and causing "flooding", which seriously affects the gas-liquid balance and electrical properties of the gas diffusion layer. However, adding dopamine to the system can significantly improve the bonding of PTFE with carbon powder and carbon fiber, thereby improving the durability of the material; (2) In-situ doping of nitrogen atoms while thermally decomposing polydopamine can also improve the conductivity of the material and improve its electrical properties.
[0070] As an embodiment, the pH value of the microporous layer slurry can be adjusted by adding one or more of sodium hydroxide solution, potassium hydroxide solution, ammonia water, triethylamine, tris buffer, sodium carbonate solution, and sodium bicarbonate solution.
[0071] As an embodiment, the solvent is one or more of water, ethanol, ethylene glycol, isopropanol, and n-propanol, but at least contains water.
[0072] In another embodiment, the present invention also relates to a method for preparing a gas diffusion layer for a hydrogen fuel cell, the method comprising the following steps:
[0073] S1, coating the hydrophobic pretreatment layer slurry onto the substrate layer, drying and high-temperature sintering;
[0074] S2, coating the first microporous layer slurry on the sample obtained in step S1, and drying;
[0075] S3, if there are two microporous layers, apply the second microporous layer slurry to the sample obtained in step S2 and dry it;
[0076] S4: Similarly, if there are multiple microporous layers, repeat steps S2 and S3;
[0077] S5. After all coating and drying steps are completed, the coating is placed in a high-temperature oven or muffle furnace for high-temperature sintering.
[0078] As an embodiment, the drying is performed at 80-120°C for 5-20 minutes; the high temperature sintering temperature is 340-400°C, and the sintering time is 10-60 minutes, preferably the high temperature sintering temperature is 370-380°C, and the sintering time is 30-40 minutes.
[0079] As an embodiment, in S1, the coating is spray coating and dip coating, and in S2 to S4, the coating is screen printing, gravure coating, slit coating, spray coating and blade coating.
[0080] Example
[0081] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Unless otherwise specified, the reagents and raw materials used can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0082] In the following examples and comparative examples, when the single cell polarization curve is tested by an electrochemical workstation, the RG11100 equipment of Riger Company is used to test the electrochemical performance of the single cell. Test conditions: battery temperature is 80°C, relative humidity is 50%, hydrogen / air stoichiometric ratio is 1.5 / 2.5, and test pressure is 1 bar. Before the test, the battery is activated in constant current mode for 4 hours. Then, the cyclic voltage method is used to test the battery performance and obtain the battery polarization curve.
[0083] Example 1
[0084] This embodiment relates to a method for preparing a gas diffusion layer for a hydrogen fuel cell, comprising the following steps:
[0085] ①Impregnate a porous carbon paper with a size of 200mm*150mm*0.17mm into a PTFE emulsion with a concentration of 5%, let it stand for 3 minutes, then take it out and dry it at 80℃ for 10 minutes to obtain a carbon paper with a PTFE content of about 10-12%, and then sinter it at 370℃ for 30 minutes to obtain a hydrophobic carbon paper;
[0086] ② Add 6.0g of conductive carbon black XC72, 6.7g of 60% PTFE emulsion, and 3.0g of dispersant TEGO 760w to a certain amount of water, stir at high speed for 20 minutes, and then disperse by ultrasound for 10 minutes to prepare a pre-dispersed microporous layer slurry with a viscosity of about 1000cp; then slowly add ammonia solution while stirring until the pH value is 8.5±0.5; add 0.9g of dopamine hydrochloride, and mechanically stir for 24 hours at room temperature; after the reaction, slowly add acetic acid water solvent to adjust the pH value of the microporous layer slurry to 6-7. The molecular weight of dopamine after polymerization was analyzed by gel permeation chromatography GPC (see Table 2), and its number average molecular weight (Mn) was 204491 and the weight average molecular weight (Mw) was 261944. The polydispersity index PD is used to measure the breadth of the molecular weight distribution of the polymer, which can be calculated by Mw / Mn. For monodisperse polymers with equal chain lengths (such as proteins), Mw / Mn=1. The synthetic polymer synthesized by optimal control (narrow molecular weight distribution polymer for calibration) should have an Mw / Mn value of 1.02 to 1.10. The Mw / Mn value of the polymer generated by stepwise polymerization is usually around 2.0. The PD of polydopamine in Example 1 is 1.28, indicating that its molecular weight distribution is relatively uniform.
[0087] Table 2: GPC molecular weight data of polydopamine of Example 1 and Example 3
[0088]
[0089] ③ The slurry prepared above is applied to the sample obtained in step ① by a scraping method, dried at 100°C for 10-15 minutes, heated to 370°C at a heating rate of 10°C / min, and sintered at this temperature for 40 minutes to obtain the target gas diffusion layer. The average thickness of the microporous layer measured by a thickness gauge is 51μm. The coating porosity can be calculated according to formula (1):
[0090]
[0091] In formula (1), is the coating porosity, W is the coating weight per unit area, S is the coating area, t is the coating thickness, and ρ is the density of the bulk material. Wherein, W = (weight after coating – weight of substrate); t = (thickness after coating – thickness of substrate).
[0092] In this embodiment, the density of carbon is ρ = 1.8 g / cm 3 By measuring the coating weight W, layer area S and thickness t, the porosity of the coating can be calculated to be 71% (see Table 3 for details).
[0093] Table 3: Data on the weight, thickness, porosity and plane resistivity of the coatings of various embodiments and comparative examples.
[0094]
[0095] Depend on Figure 4 and Figure 5 It can be seen from the microscope photos of the gas diffusion layer surface shown that compared with commercial gas diffusion layer products, the surface of the sample prepared by the present invention is smooth and uniform after high-temperature sintering, which is conducive to reducing the contact resistance between the catalyst layer and improving the battery performance. In addition, there are no obvious cracks and large pores on the surface, which can also greatly improve the durability of the product, which is a very important indicator in fuel cell applications. After the sample was soaked in 10% concentrated sulfuric acid for 1000 hours, no obvious appearance change was found, and the battery performance change was <2%. On the contrary, the microscope photos of the commercial imported gas diffusion layer products show that there are a large number of cracks on the surface of its coating. The possible reason is that the inorganic salts, small molecules or low-molecular organic matter in the slurry decompose rapidly during the heating process, generating a large number of bubbles, causing the coating surface to shrink and crack, and even partially fall off from the surface of the substrate under stress to produce peeling. After soaking in 10% concentrated sulfuric acid for 1000 hours, it was found that there was obvious precipitation of white matter on the surface of the coating and the side of the sample, and the battery performance decreased by 10-15%, reflecting the poor durability of the commercial gas diffusion layer product.
[0096] In addition, the SEM scanning electron microscope ( Figure 6 ) and pore size distribution diagram ( Figure 7) It is also easy to see that the pore size of the coating of the sample in Example 1 is concentrated in the range of 0.1 to 0.5 μm, and is monodispersed with a uniform pore structure, which is conducive to uniform dispersion and penetration of gas in the pore structure, thereby significantly improving battery performance and durability.
[0097] The plane resistivity tested by the four-probe method is 9.6mΩ·cm, indicating that the product has excellent conductivity. The single cell polarization curve ( Figure 8 ), at an operating voltage of 0.65V, the current density is 1.77A.
[0098] Example 2
[0099] This embodiment relates to a method for preparing a gas diffusion layer for a hydrogen fuel cell, comprising the following steps:
[0100] ①Impregnate a porous carbon paper with a size of 200mm*150mm*0.17mm into a PTFE emulsion with a concentration of 5%, let it stand for 3 minutes, then take it out and dry it at 80℃ for 10 minutes to obtain a carbon paper with a PTFE content of about 10-12%, and then sinter it at 370℃ for 30 minutes to obtain a hydrophobic carbon paper;
[0101] ② Add 6.0g of conductive carbon black XC72, 6.7g of 60% PTFE emulsion, and 3.0g of dispersant TEGO 760w to a certain amount of water, stir at high speed for 20 minutes, and then ultrasonically disperse for 10 minutes to prepare a pre-dispersed microporous layer slurry with a viscosity of about 1000cp; then slowly add ammonia solution while stirring until the pH value is 8.5±0.5; add 1.8g of dopamine hydrochloride and mechanically stir at room temperature for 48 hours; after the reaction is completed, slowly add acetic acid water solvent to adjust the pH value of the microporous layer slurry to 6-7.
[0102] ③ The slurry prepared above was applied to the sample obtained in step ① by a scraping method, dried at 100°C for 10-15 minutes, heated to 370°C at a heating rate of 10°C / min, and sintered at this temperature for 40 minutes to obtain the target gas diffusion layer. The average thickness of the microporous layer was measured by a thickness gauge and was 48μm. According to formula (1), the porosity of the coating was calculated to be 75%, which was increased compared with Example 1.
[0103] The plane resistivity measured by the four-probe method is 7.2 mΩ·cm, which is lower than that of Example 1. The main reason may be that the coating is doped with nitrogen atoms, which makes it have excellent conductive properties. The single cell polarization curve is tested by an electrochemical workstation ( Figure 8 ), at an operating voltage of 0.65 V, the current density is 1.94 A. Compared with Example 1, it has a higher current at the same loading voltage, indicating that the increase in porosity and conductivity is beneficial to improving the electrochemical performance.
[0104] Example 3
[0105] This embodiment relates to a method for preparing a gas diffusion layer for a hydrogen fuel cell, comprising the following steps:
[0106] ①Impregnate a porous carbon paper with a size of 200mm*150mm*0.17mm into a PTFE emulsion with a concentration of 5%, let it stand for 3 minutes, then take it out and dry it at 80℃ for 10 minutes to obtain a carbon paper with a PTFE content of about 10-12%, and then sinter it at 370℃ for 30 minutes to obtain a hydrophobic carbon paper;
[0107] ② Add 6.0g of conductive carbon black XC72, 6.7g of 60% PTFE emulsion, and 3.0g of dispersant TEGO 760w to a certain amount of water, stir at high speed for 20 minutes, and then disperse by ultrasonic for 10 minutes to prepare a pre-dispersed microporous layer slurry with a viscosity of about 1000cp; then slowly add ammonia solution while stirring until the pH value is 8.5±0.5; add 2.7g of dopamine hydrochloride, and mechanically stir for 72 hours at room temperature; after the reaction is completed, slowly add acetic acid water solvent to adjust the pH value of the microporous layer slurry to 6-7. The molecular weight of dopamine after polymerization was analyzed by gel permeation chromatography GPC (see Table 3), and its number average molecular weight (Mn) was 2161497 and the weight average molecular weight (Mw) was 2533155. Due to the increase in the proportion of dopamine addition and the extension of polymerization time, the final molecular weight of polydopamine was significantly increased (about 10 times) compared with Example 1. The polydispersity index PD is used to measure the breadth of the molecular weight distribution of a polymer, which can be calculated by Mw / Mn. For monodisperse polymers (such as proteins) with equal chain lengths, Mw / Mn=1. The Mw / Mn value of synthetic polymers synthesized with optimal control (narrow molecular weight distribution polymers for correction) should be between 1.02 and 1.10. The Mw / Mn value of polymers generated by stepwise polymerization is usually around 2.0. The PD of polydopamine in Example 3 is 1.17, indicating that its molecular weight distribution is more uniform than that in Example 1.
[0108] ③ The slurry prepared above is applied to the sample obtained in step ① by a doctor blade method, and after drying at 100°C for 10-15 minutes, it is heated to 370°C at a heating rate of 10°C / min, and sintered at this temperature for 40 minutes to obtain the target gas diffusion layer. The average thickness of the microporous layer is measured by a thickness gauge and is 50 μm. According to formula (1), the porosity of the coating can be calculated to be 78%. Compared with Example 1, its porosity is further increased, which is due to the larger and looser pore structure formed by the increase in the molecular weight of polydopamine as a pore-forming agent.
[0109] The plane resistivity measured by the four-probe method is 8.3 mΩ·cm, which is lower than that of Example 1, but slightly higher than that of Example 2. The possible reason is that the increase in the porosity of the coating has a certain effect on reducing the conductivity. The single cell polarization curve ( Figure 8 ), the current density is 1.98A at the working voltage of 0.65V. Compared with Example 1, it has a higher current at the same loading voltage, indicating that the increase in porosity and conductivity is beneficial to improving the electrochemical performance. Compared with Example 2, there is little change. The possible reason is that the increase in porosity improves the drainage performance of the gas diffusion layer, which is beneficial to the electrochemical performance; but at the same time, it leads to a decrease in conductivity, which has a certain negative effect. Therefore, the combined effect of factors makes the gas diffusion layer not continue to improve with the increase in porosity.
[0110] Example 4
[0111] A method for preparing a gas diffusion layer for a hydrogen fuel cell comprises the following steps:
[0112] ①Impregnate a porous carbon paper with a size of 200mm*150mm*0.17mm into a PTFE emulsion with a concentration of 5%, let it stand for 3 minutes, then take it out and dry it at 80℃ for 10 minutes to obtain a carbon paper with a PTFE content of about 10-12%, and then sinter it at 370℃ for 30 minutes to obtain a hydrophobic carbon paper;
[0113] ② The slurry of Example 3 is coated on the sample obtained in step ① by a doctor blade coating method, and dried at 100° C. for 10 to 15 minutes to obtain a first microporous layer with a dry film thickness of 25 to 30 μm.
[0114] ③ The slurry of Example 1 is coated on the sample obtained in step ② by a doctor blade coating method, and dried at 100° C. for 10 to 15 minutes to obtain a second microporous layer with a dry film thickness of 25 to 30 μm.
[0115] ④Then, the target gas diffusion layer is obtained by heating the coating to 370°C at a heating rate of 10°C / min and sintering at this temperature for 40 minutes. The total average thickness of the microporous layer is 53 μm as measured by a thickness gauge; the average porosity of the coating is 74% as calculated by formula (1).
[0116] The plane resistivity tested by the four-probe method is 6.7mΩ·cm, which is lower than that of Examples 1 to 3. The main reason may be that the coating is doped with nitrogen atoms, which makes it have excellent conductivity. At the same time, the gradient structure with gradually decreasing porosity from the inside to the outside ensures the flatness and density of the outer side of the coating, which is also conducive to the improvement of conductivity. The single cell polarization curve is tested by an electrochemical workstation ( Figure 8), at an operating voltage of 0.65 V, the current density is 2.12 A. Compared with Examples 1 to 3, the current density is further significantly improved at the same loading voltage, which is due to the fact that the porosity of the coating decreases from the inside to the outside, which is more conducive to the removal of water under the action of capillary force, reducing the risk of "flooding", while keeping the outer surface of the coating smooth and dense, which is conducive to reducing the surface contact resistance, and the conductive performance improvement brought by nitrogen doping and other factors.
[0117] Comparative Example 1
[0118] A method for preparing a gas diffusion layer for a hydrogen fuel cell comprises the following steps:
[0119] ①Impregnate a porous carbon paper with a size of 200mm*150mm*0.17mm into a PTFE emulsion with a concentration of 5%, let it stand for 3 minutes, then take it out and dry it at 80℃ for 10 minutes to obtain a carbon paper with a PTFE content of about 10-12%, and then sinter it at 370℃ for 30 minutes to obtain a hydrophobic carbon paper;
[0120] ② Add 6.0g of conductive carbon black XC72, 6.7g of 60% PTFE emulsion, and 3.0g of dispersant TEGO 760w into a certain amount of water, stir at high speed for 20 minutes, and then disperse by ultrasonic for 10 minutes to prepare a microporous layer slurry with a viscosity of about 1000cp.
[0121] ③ The slurry prepared above is applied to the sample obtained in step ① by a scraping method, and after drying at 100°C for 10-15 minutes, it is heated to 370°C at a heating rate of 10°C / min, and sintered at this temperature for 40 minutes to obtain the target gas diffusion layer. The average thickness of the microporous layer measured by a thickness gauge is 47μm. According to formula (1), the porosity of the coating can be calculated to be 68%. In the absence of polydopamine, the porosity of the coating is lower than that of Examples 1-4, which also shows that polydopamine can effectively play a pore-forming role.
[0122] The plane resistivity measured by the four-probe method is 15.6 mΩ·cm. In comparative example 1, no dopamine is added and no nitrogen atom is doped. Compared with examples 1 to 4, its conductivity is relatively low. The polarization curve of the single cell is tested by an electrochemical workstation ( Figure 8 ), at an operating voltage of 0.65 V, the current density is 1.46 A. Compared with Examples 1 to 4, the current density is significantly lower at the same loading voltage. This result is a good proof from the opposite side that designing a suitable coating pore structure plays a positive role in battery drainage, thereby effectively preventing the "flooding" phenomenon and improving battery performance.
[0123] Comparative Example 2
[0124] A method for preparing a gas diffusion layer for a hydrogen fuel cell comprises the following steps:
[0125] ①Impregnate a porous carbon paper with a size of 200mm*150mm*0.17mm into a PTFE emulsion with a concentration of 5%, let it stand for 3 minutes, then take it out and dry it at 80℃ for 10 minutes to obtain a carbon paper with a PTFE content of about 10-12%, and then sinter it at 370℃ for 30 minutes to obtain a hydrophobic carbon paper;
[0126] ② Add 6.0g of conductive carbon black XC72, 6.7g of 60% PTFE emulsion, and 3.0g of dispersant TEGO 760w to a certain amount of water, stir at high speed for 20 minutes, and then ultrasonically disperse for 10 minutes to prepare a pre-dispersed microporous layer slurry with a viscosity of about 1000cp; then slowly add ammonia solution while stirring until the pH value is 8.5±0.5; add 1.8g of dopamine hydrochloride and mechanically stir at room temperature for 48 hours; after the reaction is completed, keep the original pH value of the solution unchanged.
[0127] ③ After the solution was stored for 1 week, the viscosity of the solution increased to 8000cp. The slurry prepared above was applied to the sample obtained in step ① by scraping, and dried at 100℃ for 10-15 minutes, and then heated to 370℃ at a heating rate of 10℃ / min, and sintered at this temperature for 40 minutes to obtain the target gas diffusion layer. The average thickness of the microporous layer was measured by a thickness gauge and was 49μm. Since the microporous layer slurry did not adjust the pH to terminate the reaction, the viscosity of the solution increased sharply, resulting in poor leveling, uneven thickness, and uneven coating surface during film coating. Stripe defects can be observed with the naked eye. According to formula (1), the porosity of the coating can be calculated to be 72%. The reason for the reduced porosity compared with Example 2 may be that excessive self-polymerization of dopamine causes the macropores to collapse during the sintering process.
[0128] The plane resistivity tested by the four-probe method is 13.8 mΩ·cm. Compared with Example 2, although the amount of dopamine hydrochloride added is the same, the coating structure is uneven due to excessive polymerization, which is not conducive to improving conductivity. The single cell polarization curve is tested by an electrochemical workstation ( Figure 8 ), at a working voltage of 0.65 V, the current density is 1.62 A. Compared with Example 2, the current density is significantly lower at the same loading voltage, which is due to the decrease in porosity, poor drainage, and corresponding reduction in electrochemical performance.
[0129] The raw materials used in this application are all commercially available raw materials, which have a wide range of sources and can be produced on a large scale.
[0130] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.
Claims
1. A conductive paste, characterized in that: The conductive paste comprises: carbon powder, a first hydrophobic agent, a carbon black dispersant, a pore-forming agent and a solvent, wherein the pore-forming agent is polydopamine generated by adsorbing dopamine hydrochloride onto the surface of carbon powder particles by hydrogen bonding between amino groups and hydroxyl groups and undergoing in-situ self-assembly polymerization reaction in a weakly alkaline solution environment; Among them, the carbon powder accounts for 30-70% of the solid content mass percentage of the total weight of the conductive paste, the first hydrophobic agent accounts for 10-50% of the solid content mass percentage of the total weight of the conductive paste, the carbon black dispersant accounts for 30-70% of the total weight of the carbon powder, and the pore-forming agent accounts for 10-50% of the total weight of the carbon powder; The conductive paste is prepared by the following method: adjusting the pH value of a mixture of carbon powder, a first hydrophobic agent, a carbon black dispersant and a solvent to a range of 7.5 to 10, then adding dopamine hydrochloride, mechanically stirring at room temperature for 12 to 72 hours, and then adding a dilute acid solution to adjust the pH value to 6 to 7 to terminate the in-situ self-assembly polymerization reaction of the dopamine hydrochloride; When the conductive slurry is coated, dried and sintered to prepare a microporous layer, the polydopamine decomposes and forms a uniform and dense microporous structure, wherein the drying temperature is 80-120°C and the time is 5-20 minutes; the high-temperature sintering temperature is 340-400°C and the time is 10-60 minutes.
2. The conductive paste according to claim 1, characterized in that: The carbon powder accounts for 40-60% of the solid content of the conductive paste by weight; The first hydrophobic agent accounts for 20 to 40% by weight of the solid content of the total weight of the conductive paste; The carbon black dispersant accounts for 40-60% of the total weight of the carbon powder; The pore-forming agent accounts for 25-35% of the total weight of the carbon powder.
3. The conductive paste according to claim 1 or 2, characterized in that: The carbon powder is selected from one or a mixture of hydrophobically modified carbon black, acetylene black, conductive carbon black XC72, pearl black and Ketjen black; The first hydrophobic agent is selected from PTFE emulsion; The carbon black dispersant is one or more of TEGO 760w, TEGO 755w, Solsperse W210, and Solsperse W205; The solvent is water and one or more selected from the following: ethanol, ethylene glycol, isopropanol and n-propanol.
4. The method for preparing the conductive paste according to claim 1 or 2, characterized in that: The method comprises the following steps: S10: mixing carbon powder, a first hydrophobic agent, a carbon black dispersant and a solvent to obtain a first mixed solution, and adjusting the pH of the first mixed solution to 7.5-10; S20: adding dopamine hydrochloride to the first mixed solution, mechanically stirring at room temperature for 12 to 72 hours, and then adding a dilute acid solution to adjust the pH value to 6 to 7 to terminate the in-situ self-assembly polymerization reaction of the dopamine hydrochloride to obtain the conductive paste.
5. The method for preparing the conductive paste according to claim 4, characterized in that: In step S10, the pH of the first mixed solution is adjusted to 7.5-8.
5.
6. A gas diffusion layer, characterized in that: The gas diffusion layer comprises in sequence: substrate layer; and, a microporous layer disposed on the substrate layer; The substrate layer includes a second hydrophobic agent sintered at 340-400° C., the second hydrophobic agent completely penetrates into the interior of the substrate layer, and the upper surface and the lower surface of the substrate layer do not include a thin film layer with a certain thickness formed by the second hydrophobic agent; Wherein, the microporous layer is made of the conductive paste according to any one of claims 1 to 3.
7. The gas diffusion layer according to claim 6, characterized in that The microporous layer includes at least a first microporous layer and a second microporous layer, the first microporous layer is closer to the substrate layer than the second microporous layer, and the porosity and pore size of the micropores of the microporous layer gradually decrease along the direction from the first microporous layer to the second microporous layer.
8. The gas diffusion layer according to claim 6 or 7, characterized in that: The substrate layer includes one or more of the following: carbon fiber paper, carbon fiber non-woven fabric, and carbon fiber braid.
9. The gas diffusion layer according to claim 6, characterized in that When the microporous layer is a single-layer microporous layer, the thickness thereof is 10 to 100 μm; when the microporous layer is two or more microporous layers, the total thickness thereof is 10 to 100 μm.
10. The gas diffusion layer according to claim 6, characterized in that When the microporous layer is a single-layer microporous layer, the thickness thereof is 20 to 80 μm; when the microporous layer is two or more microporous layers, the total thickness thereof is 20 to 80 μm.
11. The gas diffusion layer according to claim 6, characterized in that When the microporous layer is a single-layer microporous layer, the thickness thereof is 30 to 70 μm; when the microporous layer is two or more microporous layers, the total thickness thereof is 30 to 70 μm.
12. The method for preparing a gas diffusion layer according to any one of claims 6 to 11, characterized in that: The preparation method comprises the following steps: S1, coating the hydrophobic pretreatment layer slurry onto the substrate layer, drying and sintering at high temperature; S2, coating the first microporous layer slurry on the sample obtained in step S1, and drying; S3, if there are two microporous layers, apply the second microporous layer slurry to the sample obtained in step S2 and dry it; S4: And so on, if there are more than two microporous layers, repeat steps S2 and S3; S5. After all coating and drying steps are completed, the coating is placed in a high-temperature oven or muffle furnace for high-temperature sintering.
13. The preparation method according to claim 12, characterized in that: The drying is performed at 80-120° C. for 5-20 minutes; the high-temperature sintering temperature is 340-400° C., and the sintering time is 10-60 minutes.
14. The preparation method according to claim 13, characterized in that: The high temperature sintering temperature is 370-380° C., and the sintering time is 30-40 minutes.
15. The preparation method according to claim 12, characterized in that: In step S1, the coating is spray coating and dip coating, and in S2 to S4, the coating is screen printing, gravure coating, slit coating, spray coating or blade coating.
16. A hydrogen fuel cell, characterized in that: The method comprises the gas diffusion layer according to any one of claims 6 to 11.
Citation Information
Patent Citations
Gaseous diffusion layer of proton exchange membrane fuel cell and preparation method thereof
CN102024961A
Method for preparing double-microporous layers for improving performance of fuel batteries
CN106299398A
Gas diffusion layer, preparation method thereof, corresponding membrane electrode assembly and fuel cell
CN111584879A